2019
DOI: 10.1093/mnras/stz1843
|View full text |Cite
|
Sign up to set email alerts
|

Observational properties of ultra-diffuse galaxies in low-density environments: field UDGs are predominantly blue and star forming

Abstract: Abstract While we have learnt much about ultradiffuse galaxies (UDGs) in groups and clusters, relatively little is known about them in less dense environments. More isolated UDGs are important for our understanding of UDG formation scenarios because they form via secular mechanisms, allowing us to determine the relative importance of environmentally driven formation in groups and clusters. We have used the public Kilo-Degree Survey together with the Hyper Suprime… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(81 citation statements)
references
References 107 publications
(200 reference statements)
6
73
0
Order By: Relevance
“…An approximately linear dependence between the abundance of UDGs in galaxy clusters and the cluster mass was found (van der Burg et al 2017;Janssens et al 2017;Román & Trujillo 2017). Within clusters, UDGs appear to be found on the red sequence (van Dokkum et al 2015a;van der Burg et al 2016), while UDG-like galaxies found in the field typically appear to be bluer (Leisman et al 2017;Prole et al 2019).…”
Section: Introductionmentioning
confidence: 92%
“…An approximately linear dependence between the abundance of UDGs in galaxy clusters and the cluster mass was found (van der Burg et al 2017;Janssens et al 2017;Román & Trujillo 2017). Within clusters, UDGs appear to be found on the red sequence (van Dokkum et al 2015a;van der Burg et al 2016), while UDG-like galaxies found in the field typically appear to be bluer (Leisman et al 2017;Prole et al 2019).…”
Section: Introductionmentioning
confidence: 92%
“…In the limited available examples of field UDGs, however, the reported luminosity-weighted ages have consistently been younger, with ages ranging from 1 to 3 Gyr (Martínez-Delgado et al 2016;Greco et al 2018;Martín-Navarro et al 2019). In fact, the UDG population in the field is expected to have a larger variety of colors than that of the clusters (Di Cintio et al 2017) and there is observational support for this trend (van der Burg et al 2016;Prole et al 2019).…”
Section: The Luminosity-weighted Ages Of Field Udgsmentioning
confidence: 99%
“…Photometric information, such as broadband colors (e.g. Prole et al 2019), are available for many UDGs but are of limited value in determining the properties of the stellar populations, while spectroscopy, which can provide the necessary information, is only available for a small number of galaxies (e.g. Martínez-Delgado et al 2016;Kadowaki et al 2017;Ruiz-Lara et al 2018;Ferré-Mateu et al 2018;Gu et al 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Novel development of automated detection algorithms show promising results. One of the best software packages available today is MTObjects (Teeninga et al 2013(Teeninga et al , 2015, a max-tree based algorithm developed for medical image analysis and rewritten for astronomical purposes (see, e.g., Prole et al 2019). It is non-parametric; that is, it automatically searches for the best parameters for a given image, which makes MTObjects straightforward to use.…”
Section: Automated Detection With Mtobjectsmentioning
confidence: 99%
“…Several surveys have targeted the more prominent of these giant galaxies like M 83 (Müller et al 2015), Centaurus A (Crnojević et al 2014(Crnojević et al , 2016Müller et al 2017;Taylor et al 2018), and others (Merritt et al 2014;Karachentsev et al 2015;Javanmardi et al 2016;Park et al 2017;Smercina et al 2018;Bennet et al 2019;Carlsten et al 2020;Davis et al 2020). Furthermore, dwarf galaxy surveys reach even more distant galaxy clusters (Venhola et al 2017;Wittmann et al 2019), groups (Geha et al 2017;Cohen et al 2018;Habas et al 2020), and the field (Greco et al 2018;Prole et al 2019).…”
Section: Introductionmentioning
confidence: 99%